THE ROLE OF STUDENT MOTIVATION IN THE MODERN EDUCATIONAL PROCESS - Muratova Dilorom Mahmudovna; Kayratov Nursultan (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation: Student motivation is one of the most important factors in the modern educational process. It has a direct influence on academic performance, learning activity, and the overall development of a student’s personality. In today’s educational environment, where information is easily accessible and teaching methods are constantly changing, motivating students becomes a key task for educators. This article examines the concept of student motivation, its main types, and effective ways to increase motivation in the learning process. Special attention is given to the role of the teacher, modern teaching methods, and the creation of a positive educational environment that supports students’ interest in learning.